THERMOSENSITIVE IN SITU GEL OF TINIDAZOLE IN TREATMENT OF BACTERIAL VAGINOSIS: FORMULATION AND EVALUATION (International Journal of Ayurveda and Pharma Research, 2020)
Bacterial Vaginosis (BV) is the leading cause of vaginal discharge. Because of its big surface area, wealthy blood supply, avoidance of the first-pass effect and high permeability to many drugs, the vagina offers a promising location for local impact as well as systemic drug delivery. In situ gels give several benefits, such as ease of administration in the respective body cavities, elevated spreadability at certain temperatures, reduced administration frequency, improved patient compliance and comfort compared to standard dosage forms. Tinidazole (TNZ) can give effective treatment over the BV. In situ gel of TNZ containing polaxomer 407 and HPMC E100 or carbopol 941NF was optimized on the basis of various evaluation parameters. Gelation temperature (Tgel) and pH of all batches was found in range of 36.6 to 38.0 ºC and 4.20 to 5.03, viscosity was found in range of 1100-2050 cps at 25ºC and 4800-6530 cps at 37ºC. The Spredability was found in range of 16-20 cm. From these evaluation parameters we selected best combination for the mucoadhesive property, antimicrobial study, in vitro drug release and for HET CAM irritation study. The optimized formulation gives satisfactory results. In this study we also compare the performance of two mucoadhesive polymer. Based on maximum desirability and cost effectiveness, in situ vaginal gel containing 20% polaxomer and 0.5% HPMC E100 could be considered as a highly promising treatment for bacterial vaginosis.